Implementasi Model Pembelajaran Berbasis Proyek dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Pancasila di SMAN 1 Gorontalo - Safira Loupe; Zulaecha Ngiu; Yuli Adhani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Critical thinking is one of the most important skills needed by Pancasila Education students to face 21st-century challenges. However, teacher-dominated learning methods have hindered students from fully developing these skills. Therefore, this study aims to implement the Project-Based Learning (PjBL) model in Pancasila Education at SMA Negeri 1 Gorontalo City to improve critical thinking skills. This research uses a Classroom Action Research (CAR) approach conducted in two cycles consisting of planning, implementation, observation, and reflection stages based on Kemmis and McTaggart’s model. The subjects were 20 students. Data were collected through observation, tests, documentation, and field notes, then analyzed using qualitative and quantitative descriptive techniques. The results show that the PjBL model significantly improved critical thinking skills, indicated by the increase in students categorized as high-level thinkers from 24% to 92% by Cycle II. In addition, the average learning outcomes increased from 63.84 to 87.00, while classical completeness reached 92%. These findings indicate that PjBL, emphasizing active learning, collaboration, and project completion, is effective in improving both critical thinking skills and learning outcomes. Therefore, PjBL can be recommended as a differentiated instructional strategy to enhance the quality of Pancasila Education in secondary schools.